1977
DOI: 10.1007/bf02535449
|View full text |Cite
|
Sign up to set email alerts
|

The effect of various dietary factors on the size distribution of lymph fat particles in rat

Abstract: By means of cellulose acetate electrophoresis and measurement of radio-activity, lipoproteins (d less than or equal to 1,006) of lymph collected from rats fed a diet containing fats added to labeled fatty acids for 20-24 hr, have been separated into two kinds differing in their size. Fats with different saturated and unsaturated fatty acid content were tested: corn oil, lard, mutton tallow, tripalmitin, corn oil-lard mixture, and randomized palmitic-linoleic triglycerides. Factors studied were: (a) increased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Unsaturated fatty acids, which have a lower melting point and a greater affinity for the fatty acid-binding protein (Ockner & Manning, 1976), are transported more rapidly and should thus give rise to larger chylomicrons than SFA. Experiments conducted in the rat have yielded contrasting results, some claiming no impact of fat saturation (Fraser et al 1968;Renner et al 1986), others finding larger particles after unsaturated fatty acids (Boquillon et al 1977;Feldman et al 1983;Levy et al 1991;Kalogeris & Story, I992a,b). Few data were available for human subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsaturated fatty acids, which have a lower melting point and a greater affinity for the fatty acid-binding protein (Ockner & Manning, 1976), are transported more rapidly and should thus give rise to larger chylomicrons than SFA. Experiments conducted in the rat have yielded contrasting results, some claiming no impact of fat saturation (Fraser et al 1968;Renner et al 1986), others finding larger particles after unsaturated fatty acids (Boquillon et al 1977;Feldman et al 1983;Levy et al 1991;Kalogeris & Story, I992a,b). Few data were available for human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The size of triacylglycerol (TG)-rich lipoproteins (TRL) is largely determined by the rapidity of TG overall absorption, as apolipoprotein (apo) B synthesis appears to be essentially constant (Hayashi et al 1990); large TRL are produced when amounts of TG increase (Boquillon et al \911;Bennett-Clark & Norum, 1978;Hayashi et al 1990). Also, the quality of ingested or infused TG affects TRL size; large chylomicrons are produced after ingestion of polyunsaturated fatty acids (PUFA), compared with VLDL-size particles secreted after ingestion of saturated fatty acids (SFA) (Boquillon et al 1977;Feldman et al 1983;Levy et al 1991;Kalogeris & Story, 1992a) which are characterized by an elevated phospholipid (PL): TG ratio (Kalogeris & Story, 1992a). On the other hand, large size and/ or PUFA-rich chylomicrons are rapidly cleared from serum compared with small and/or SFA-rich chylomicrons (Groot et al 1988;Weintraub et al 1988;Levy et al 1991) due to differences in susceptibility to lipolytic enzymes (Coiffier et al 1987;Weintraub et al 1988).…”
mentioning
confidence: 99%
“…Particulates in blood passing through the liver are prevented from direct access to the hepatocytes if they are larger than the fenestrations lining the lobule sinusoid. Saturated dietary fat has been shown to result in smaller chylomicrons from rat intestine than when unsaturated fat is fed (Boquillon et al 1977). A parallel situation in fowl would effect a differential access by VLDL to hepatocytes and permit selective modifications in fatty acid composition.…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…This shift in cholesterol partitioning could slow the absorption of cholesterol from a micellar solution and would result in decreased absorption into mesenteric lymph. In addition, fatty acids and lecithin have been shown to increase the physical size of the micellar particles (Nakayama and Miyaki, 1965 (Boquillon et al, 1974) and electrophoretic (Boquillon et al, 1972;Boquillon et al, 1977) studies have shown that feeding saturated fat leads to production of smaller absorptive lipoproteins. The size of absorptive lipoproteins is of interest in view of the finding that large, triglyceride-rich lipoproteins are cleared more rapidly from plasma than are small ones Havel and Kane, 1975).…”
mentioning
confidence: 99%